The fundamental principles and classification of modern methodological approaches to strategic innovation changes in construction projects and their key participants - Stelmakh , O.; Hura, O.; Borodavka, O.; Gega , S. (Ways to Improve Construction Efficiency, 2024)
This article focuses on analyzing the core principles and approaches to strategic innovation changes in construction projects. It highlights the methodological foundations that define the effectiveness of construction project management in a changing market environment and the integration of innovations into the activities of key market participants, such as developers, contractors, investors, and end-users. Given that the construction industry is one of the most capital-intensive and complex sectors to manage, strategic innovations can provide significant competitive advantages and cost reduction. The article discusses key methodological approaches to implementing changes in construction project management, particularly the use of integrated management models, the application of digital technologies, and new approaches to project financing and implementation. It also emphasizes the importance of flexible strategies that enable adaptation to market changes, environmental requirements, and technological innovations. As a result, the article outlines the significance of strategic management and innovations for the development of construction projects and improving their efficiency. This paper also highlights the key challenges faced by construction market participants when implementing innovative strategies in construction project management. One of the main challenges is the need to adapt to rapid changes in the economic and technological environment, which requires flexibility in management and the ability to quickly respond to new market demands. Considering the high capital intensity of construction projects, enterprises must focus on effective resource and investment management, which is only possible through the introduction of innovative methods and technologies. Important aspects include the use of digital tools, such as Building Information Modeling (BIM), management automation systems, big data analytics (Big Data), and Internet of Things (IoT) technologies, which allow optimizing processes, reducing costs, and improving the quality of work execution. The article also examines the importance of integrating stakeholders into the project management process, which helps create more transparent and effective conditions for all market participants. Involving investors, contractors, and end-users in decision-making processes helps reduce risks and improve the efficiency of interaction among all parties. Considering their interests and integrating with the latest project management approaches are key elements for achieving long-term success in the construction market. As a result, the article provides recommendations for improving construction project management through the integration of innovative strategies, including the latest technologies and flexible management strategies that contribute to increased efficiency, cost reduction, and enhanced competitiveness of construction enterprises.